Higher 2nd life Lithium Titanate battery content in hybrid energy storage systems lowers environmental-economic impact and balances eco-efficiency. (December 2021) - Koh, S.C.L.; Smith, L.; Miah, J.; Astudillo, D.; Eufrasio, R.M.; Gladwin, D.; Brown, S.; Stone, D.
Abstract: Energy exchange technologies will play an important role in the transition towards localised, sustainable energy supply. Hybrid energy storage systems, using different energy storage technologies, are currently under investigation to improve their technical performance and environmental sustainability. However, there is currently no exploration of the environmental benefits and economic feasibility of hybrid energy storage systems combining 1 st and 2 nd life batteries and battery electric vehicles. To determine the environmental and economic impacts of this type of hybrid energy storage system, this research employs a three-tier circularity assessment incorporating Life Cycle Assessment, Techno Economic Analysis and an Eco-Efficiency Index, from cradle-to-grave, of 43 techno-hybridisations of four 1 st and 2 nd life battery technologies; Lithium Titanate, Lead-acid, Lithium Iron Phosphate and Sodium-ion, with battery electric vehicles. The results of the life cycle assessment and techno-economic analysis show that a hybrid energy storage system configuration containing a low proportion of 1 st life Lithium Titanate and battery electric vehicle battery technologies with a high proportion of 2 nd life Lithium Titanate batteries minimises the environmental and economic impacts and provides a high eco-efficiency. The results of the eco-efficiency index show that a hybrid energy storage system configuration containing equal proportions of 1 st and 2 nd life Lithium Titanate and BEV battery technologies is the most eco-efficient. This research highlights the environmental and economic benefits of the use of Lithium Titanate battery technologies within novel hybrid energy storage systems. Highlights: Three-tier circularity of a hybrid energy storage system (HESS) assessed. High 2nd life battery content reduces environmental and economic impacts. Eco-efficiency index results promote a high 2nd life battery content. Lithium titanate (LTO) HESS has the lowest environmental and economic impacts. LTO HESS balances eco-efficiency index.